The Influence of Price, Promotion, and Product Quality on Purchasing Decisions at Toko Sahabat Sasirangan Martapura, Banjar Regency - Kadir, Abdul; Audah, Ali; Faridah, Faridah (Universitas Hang Tuah, 2026)
This study examines the partial and simultaneous effects of price, promotion, and product quality on purchase decisions at Sahabat Sasirangan Store Martapura, Banjar Regency. This quantitative study used questionnaires to collect data from 68 consumers selected through purposive sampling. Data were analyzed using multiple linear regression, t-test, F-test, and the coefficient of determination with SPSS. The results indicate that price, promotion, and product quality each have a positive and significant effect on purchase decisions, with significance values of 0.000 < 0.05. Simultaneously, the three variables significantly affect purchase decisions, as indicated by an F-count of 58.772 and significance of 0.000 < 0.05. The Adjusted R Square of 0.936 shows that 93.6% of the variation in purchase decisions is explained by price, promotion, and product quality. Price is the most dominant variable influencing purchase decisions. Therefore, Sahabat Sasirangan Store should maintain competitive pricing, strengthen social media promotion, and ensure consistent product quality to encourage consumer purchase decisions.